2001
DOI: 10.1068/b2642r
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Effects of Built Environment on Bus Stop Crime

Abstract: There has been considerable interest in recent decades for the identification of the physical correlates of crime in different urban settings. This study focuses on bus stop crime and seeks to understand how different environmental attributes in the vicinity of a bus stop can affect the incidence of crime. We first review evidence from the relevant literature to understand the impacts of built environment on crime. This is followed by the presentation of our empirical research. We have used a stratified random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 26 publications
1
42
0
1
Order By: Relevance
“…This particularly relates to land uses that have the tendency to generate crime, such as prisons, pubs, bottle shops (off-licenses), pharmacies, seedy hotels, vacant lots/buildings, and cash converters/pawn shops (Newton 2014). This also has been observed in relation to public transport with regard to bus stops (Loukaitou-Sideris 1999;Loukaitou-Sideris et al 2001). However, it has been asserted that reference to the wider environment and geographical juxtaposition is lacking in the CPTED literature and, consequently, is rarely considered in the design of urban spaces (Cozens 2014).…”
Section: Cpted and Component Conceptsmentioning
confidence: 94%
“…This particularly relates to land uses that have the tendency to generate crime, such as prisons, pubs, bottle shops (off-licenses), pharmacies, seedy hotels, vacant lots/buildings, and cash converters/pawn shops (Newton 2014). This also has been observed in relation to public transport with regard to bus stops (Loukaitou-Sideris 1999;Loukaitou-Sideris et al 2001). However, it has been asserted that reference to the wider environment and geographical juxtaposition is lacking in the CPTED literature and, consequently, is rarely considered in the design of urban spaces (Cozens 2014).…”
Section: Cpted and Component Conceptsmentioning
confidence: 94%
“…With few exceptions (Block and Block 2000;Block and Davis 1996;Loukaitou-Sideris and Banerjee 2000), researchers have ignored the spatial environment (type of land uses, urban form attributes) in the immediate vicinity of transit stations. As previous research has shown, there is a correlation of certain environmental attributes with bus stop crime (Loukaitou-Sideris 1999;Loukaitou-Sideris et al 2001;Liggett, Loukaitou-Sideris, and Iseki 2001). In fact, such a station is not too different from a bus stop.…”
mentioning
confidence: 91%
“…In a spatio-temporal context, urban planners should consider how the physical characteristics and activity functions of land uses change over time. For example, urban planners and designers should ensure that foliage and event-related infrastructure in parks during the summer does not obscure the natural surveillance provided by vehicular traffic, passersby, and park users (Loukaitou-Sideris et al, 2001;Iqbal and Ceccato, 2016).…”
Section: Spatio-temporal Crime Patterns and Time-varying Regression Cmentioning
confidence: 99%
“…Future research should investigate data that directly captures both spatial and temporal dimensions of routine activities, such as sales data from commercial retail stores (Weisburd et al, 2012), statistics on park users or transit ridership (Loukaitou-Sideris et al, 2001), or mobile phone and social media data that captures business check-ins (Hanaoka, 2016;Jacobs-Crisioni et al, 2014). It may also be interesting to explore spatio-temporal crime patterns during longer processes of metropolitan or neighbourhood change, for example modeling the time-varying effects of changing sociodemographic characteristics related to gentrification (Kirk and Laub, 2010;Papachristos et al, 2011).…”
Section: Limitations and Future Researchmentioning
confidence: 99%